Spanda-kārikā : Bhaṭṭakallaṭācārya viracita vr̥tti sahita - Vasugupta (Motīlāl Banārasīdās, 1981)
Verse exposition, with commentaries, on Vasugupta's Śivasūtra, basic work of the Trika philosophy in Kashmir Saivism.